A new bipolar ice core record of volcanism from WAIS Divide and NEEM and implications for climate forcing of the last 2000 years. Issue 3 (7th February 2013) - Sigl, Michael; McConnell, Joseph R.; Layman, Lawrence; Maselli, Olivia; McGwire, Ken; Pasteris, Daniel; Dahl‐Jensen, Dorthe; Steffensen, Jørgen Peder; Vinther, Bo; Edwards, Ross; Mulvaney, Robert; Kipfstuhl, Sepp
Abstract : [1] Volcanism is a natural climate forcing causing short‐term variations in temperatures. Histories of volcanic eruptions are needed to quantify their role in climate variability and assess human impacts. We present two new seasonally resolved, annually dated non‐sea‐salt sulfur records from polar ice cores—WAIS Divide (WDC06A) from West Antarctica spanning 408 B.C.E. to 2003 C.E. and NEEM (NEEM‐2011‐S1) from Greenland spanning 78 to 1997 C.E.—both analyzed using high‐resolution continuous flow analysis coupled to two mass spectrometers. The high dating accuracy allowed placing the large bi‐hemispheric deposition event ascribed to the eruption of Kuwae in Vanuatu (previously thought to be 1452/1453 C.E. and used as a tie‐point in ice core dating) into the year 1458/1459 C.E. This new age is consistent with an independent ice core timescale from Law Dome and explains an apparent delayed response in tree rings to this volcanic event. A second volcanic event is detected in 1453 C.E. in both ice cores. We show for the first time ice core signals in Greenland and Antarctica from the strong eruption of Taupo in New Zealand in 232 C.E. In total, 133 volcanic events were extracted from WDC06A and 138 from NEEM‐2011‐S1, with 50 ice core signals—predominantly from tropical source volcanoes—identified simultaneously in both records. We assess the effect of large bipolar events on temperature‐sensitive tree ring proxies. These two new volcanic records, synchronized with available ice core records to account for spatial variability in sulfate deposition, provide a basis for improving existing time series of volcanic forcing. Key Points: High accuracy history of explosive volcanism in the last 2000 years Reinterpretation of volcanic signals widely used as stratigraphic time markers Annual layer counted timescale for WAIS Divide ice core from 0‐577m